Anti-nociceptive and antipyretic activities of Solanum violaceum ortega - Karim, Afroz; Islam, Baharul; Tareq, Syed; Islam, Muhammad (International Journal of Medicine, 2017)
Solanum violaceum Ortega has been used by the traditional medicine practitioners in pain and fever. This study aimed at investigating anti-nociceptive and antipyretic activities of methanol extract of leaf (MELSV), fruit (MEFSV) and root (MERSV) of S. violaceum in Swiss albino mice. Anti-nociceptive activity was evaluated using hot plate method while antipyretic by brewer’s yeast induced hyperpyrexia. In both tests, test animals were divided into eight groups of six in each. The groups were treated as negative control (distilled water), standard and tests (250 and 500 mg/kg of MELSV/ MERSV/ MERSV). Diclofenac sodium (150 mg/kg) and paracetamol (150 mg/kg) were taken as standards for anti-nociceptive and antipyretic tests, respectively. All the treatments were administrated via oral gavages (p.o.). Results suggest that, the plant extracts dose-dependently increased retention time compared to the control groups. MELSV at 500 mg/kg significantly increased retention time on the hot-pate of the test animals than the MEFSV and MERSV treated groups. In the antipyretic test, both 250 and 500 mg/kg of MELSV and 500 mg/kg of MEFSV significantly (p <0.05) decreased temperature to the experimental animals 30, 60, 120 minutes. In conclusion, the crude extracts of S. violaceum exhibited anti-nociceptive and antipyretic activities. S. violaceum may be one of the good sources of anti-nociceptive and antipyretic compounds.